THE EFFECT OF MUSTARD GREENS POWDER AND PELLETS ON THE GROWTH OF COMMON CARP (Cyprinus carpio) Fry - Ningsih, Ayu Candra; Sari, Annisa Novita; Jailani, Abdul Qadir (Asian Journal of Aquatic Sciences, 2023)
Common carp is a fish consumption that is relatively easy to cultivate since it tends to be adaptive (easy to adapt to its environment and resistant to various types of diseases). One of the protein requirements for the growth of fish seeds can be obtained from mustard greens. Furthermore, the abundant availability of mustard greens in Kajoran Village can be an alternative feed if developed as carp feed. The purpose of this study is to determine the effect of mustard greens powder on the growth of common carp (Cyprinus carpio); besides, to determine the best concentration of mustard greens powder on the growth of common carp. This study was conducted in January-February 2022. The research method used an experimental method with treatment P1 (control), P2 (mustard green powder 25%), P3 (50%), P4 (75%), and P5 (100%). The results of giving the concentration of mustard green powder for the growth of common carp show a significant difference and it can increase the growth of carp. Furthermore, the best treatment is achieved in the P3 treatment (50% mustard green powder) with an average weight gain of 1.120 g. From the results of this study, it is expected that the people of Kajoran Village can use mustard greens well for carp cultivation with a concentration of 50% pellets and 50% mustard green powder. In addition, further research is needed on the manufacture of pellets from mustard green powder to make it easier for farmers to feed.